The genetic control of Aedes aegypti - Haghighat-Khah, R (2013)
In the last century, we have observed the introduction, establishment and expansion of mosquito-borne diseases into diverse new geographic ranges. The utility of genetically engineered mosquitoes as tools to decrease the burden of disease by controlling disease-transmitting vectors is being evaluated. The work in this thesis contributes to this goal by exploring mechanisms to spread (or 'drive') anti-pathogenic traits (i.e. disease refractoriness) into target populations through the use of an engineered gene drive system in Aedes aegypti, and by developing additional tools for the safe, reliable, and targeted transformation of these mosquitoes for field release using a novel site-specific cassette exchange mechanism. The proposed gene drive system is underdominance-like as it relies on the inheritance of a pair of trans-suppressing lethal constructs, and uses a novel design to help tackle the 'linkage problem', which is the potential dissociation of the drive system and its 'cargo' anti-pathogenic gene(s). One component of this proposed gene drive system is a lethal or fitness-reducing gene. A range of effector proteins with different biochemical modes of action was screened for their suitability in this system. Effectors that looked promising in this initial screen were evaluated further for their phenotypes when expressed under the control of selected blood-meal inducible promoters. One combination gave the interesting and novel phenotype of temporary blood-meal-induced paralysis. Partial suppression of effector expression was achieved by co-expressing a hairpin RNA for RNA interference, however it proved difficult to combine adequate fitness penalty and rescue to the degree required for a field-usable system. The cassette exchange system combines the ΦC31-att integration system, and Cre or FLP-mediated excision to remove extraneous sequences introduced as part of the site-specific integration process. This provides a useful new tool for genome manipulation. Complete cassette exchange was achieved and the absence of any obvious fitness costs or positional effects in two docking strains make these lines good candidates for both research and generation of new transgenic strains for genetic control of Ae. aegypti.